Clinical Consensus Statement: Balloon Dilation of the Eustachian Tube. (July 2019) - Tucci, Debara L.; McCoul, Edward D.; Rosenfeld, Richard M.; Tunkel, David E.; Batra, Pete S.; Chandrasekhar, Sujana S.; Cordes, Susan R.; Eshraghi, Adrien A.; Kaylie, David; Lal, Devyani; Lee, Jivianne; Setzen, Michael; et al.
Objective: To develop a clinical consensus statement on the use of balloon dilation of the eustachian tube (BDET). Methods: An expert panel of otolaryngologists was assembled with nominated representatives of general otolaryngology and relevant subspecialty societies. The target population was adults 18 years or older who are candidates for BDET because of obstructive eustachian tube dysfunction (OETD) in 1 or both ears for 3 months or longer that significantly affects quality of life or functional health status. A modified Delphi method was used to distill expert opinion into clinical statements that met a standardized definition of consensus. Results: After 3 iterative Delphi method surveys, 28 statements met the predefined criteria for consensus, while 28 statements did not. The clinical statements were grouped into 3 categories for the purposes of presentation and discussion: (1) patient criteria, (2) perioperative considerations, and (3) outcomes. Conclusion: This panel reached consensus on several statements that clarify diagnosis and perioperative management of OETD. Lack of consensus on other statements likely reflects knowledge gaps regarding the role of BDET in managing OETD. Expert panel consensus may provide helpful information for the otolaryngologist considering the use of BDET for the management of patients with OETD.